(untitled) (Research, Society and Development, 2021)
Autoimmune polyglandular syndromes (APSS) are associations of two or more endocrine diseases of autoimmune origin that affect between 5-10% of the population. The grouping of these diseases depends on genetic and environmental factors, their different presentations allow the distinction of the subtypes of APS. The objective is to report the case of a patient with type III A polyglandular autoimmune syndrome, characterized by Hashimoto’s thyroiditis and type 1 diabetes mellitus associated with hyperprolactinemia and Gilbert’s syndrome. The patient began to show the symptoms of the syndrome at the age of 10 progressively. The treatment of each disease is being carried out, with no specific treatment for the syndrome in the literature.